2014
DOI: 10.1002/hed.23519
|View full text |Cite
|
Sign up to set email alerts
|

Supraglottic immunoglobulin-G4 related plasma cell granuloma: Case report and literature review

Abstract: Because IgG4 testing is not performed routinely, management recommendations have been poorly defined. We reviewed the literature and discuss herein the clinical characteristics, pathology, diagnosis, and management. The authors theorize that IgG4-related disease involving the larynx and pharynx may be more common than suggested by the paucity of reported cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 11 publications
(21 reference statements)
3
23
0
1
Order By: Relevance
“…Upper respiratory tract presentation of the disease is rare (Table I) [3,8,9,11,12,13,14,15,16]. A review of the available literature showed only single cases of IgG4-RD of the oral cavity with presentation in the palate, tongue, floor of the mouth, and upper and lower gingiva [3,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Upper respiratory tract presentation of the disease is rare (Table I) [3,8,9,11,12,13,14,15,16]. A review of the available literature showed only single cases of IgG4-RD of the oral cavity with presentation in the palate, tongue, floor of the mouth, and upper and lower gingiva [3,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…13 IgG4-related disease has been observed in nearly every organ, including the biliary system, thyroid, salivary glands, kidneys, lungs, skin, lymph nodes, and orbital tissues. 14 Airway involvement has been described in the nasal cavity, trachea, and lungs 8,10,15,16 and seldom in the larynx, 7,17 with no reports of isolated pharyngeal involvement. In addition, previously named entities such as Mikulicz's syndrome, Küttner's tumor, Riedel's thyroiditis, and inflammatory pseudotumor (including orbital pseudotumor) have now been recognized to be a part of the IgG4-RD spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 11 reports describing cases of laryngotracheal involvement due to IgG4-RD [16][17][18][19][20][21][22][23][24][25][26], 2 of them written in a non-English language [22,25]. Table 1 includes an update of the published cases written in English [16-21, 23, 24, 26].…”
Section: Resultsmentioning
confidence: 99%
“…We found a total of 12 patients with laryngopharyngeal involvement, most of them adult men. The most common sites of IgG4 + plasma cell infiltration were the pharynx [16,19,21] and the supraglottic region of the larynx [17,20,21,24]. Treatment strategies included local surgery and immunosuppressive drugs.…”
Section: Resultsmentioning
confidence: 99%